2023
DOI: 10.21203/rs.3.rs-2310316/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Network Analysis of Host Genetic Risk Variants of Severe COVID-19

Abstract: Background: Genome-wide association studies have identified numerous human host genetic risk variants that play a substantial role in the host immune response to SARS-CoV-2. Although these genetic risk variants significantly increase the severity of COVID-19, their influence on body systems is poorly understood. Therefore, we aim to interpret the biological mechanisms and pathways associated with the genetic risk factors and immune responses in severe COVID-19. We perform a deep analysis of previously identifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…RA also has an association with infections such as Mycoplasma, Epstein-Barr virus, Helicobacter pylori, and COVID-19 [12,13]. Such infections can trigger the activation of T cells and regulate the secretion of autoantibodies such as rheumatoid factors, which contribute to the pathogenesis of RA [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA also has an association with infections such as Mycoplasma, Epstein-Barr virus, Helicobacter pylori, and COVID-19 [12,13]. Such infections can trigger the activation of T cells and regulate the secretion of autoantibodies such as rheumatoid factors, which contribute to the pathogenesis of RA [13].…”
Section: Introductionmentioning
confidence: 99%
“…Further research has also linked neurological diseases such as multiple sclerosis (MS) and Alzheimer's disease (AD) with RA. In patients with MS, dysfunction of the immune system leads to antigen-specific activation and secretion of inflammatory cytokines that create a chronic systemic inflammatory state, which consequently increases the risk of developing RA [12,16]. Although RA and AD are different conditions, genetic studies have revealed a few key genes commonly associated with both RA and AD [16][17][18].…”
Section: Introductionmentioning
confidence: 99%